Information needs and information seeking behaviour of rural dwellers in Sarawak, Malaysia - Yap, Ching Seng; Huong Tiew, Fidella Nga; Ngadan, Alpha Anak; Ho, Poh Ling (Malaysian Journal of Library and Information Science, 2020)
This research aims to investigate the information needs and information seeking behaviour of the rural dwellers in Sarawak focusing on identifying their information needs; examining their use of information sources; assessing their perception of quality and accessibility of the information sources; and determining the barriers to information seeking. An interviewer-administered questionnaire survey is adopted for data collection, from the rural dwellers, covering broadly the northern, central, and southern regions of Sarawak. This study covers a broader range of information needs (12 types) and use of information sources (20 sources) of the rural dwellers in Sarawak. Using a quota sampling technique based on geographical region, data are collected from 130 respondents in each region, a total of 390 respondents. This paper reports the research findings using descriptive statistical analysis. The rural dwellers have the highest needs in the area of religion, health and medical, as well as entertainment, leisure, and sports. They have the lowest needs for information about social welfare, politics, and general/state election. The popularity of digital sources such as the Internet, social media, and mobile applications have become the main source of information seeking of the rural dwellers, with the traditional sources such as television, radio, and newspapers are still being widely used. When the perception of information source quality and accessibility is high, the frequency of using the source for information seeking is also high. Poor infrastructure and limited financial ability are cited as the main barriers to information seeking among the rural dwellers.